ANIMATION AND VIDEO IN IMPROVING OPEN WORDS VOCABULARY - MARLIN STEFFI MARPAUNG (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2021)
The most important part of language learning is vocabulary. To do well in English and effectively perform a good English, students must be able to retain words. The purpose of this study is to seek whether vocabulary learning through animation and video in groups learning perform better than individual learning. This study used a quantitative analysis approach with a comparison design to find out the students' vocabulary enhancement. The vocabulary pre-test and post-tests were utilized as the instruments of this study. The sample were VIII grade students from two classes at a public school in Cimahi, Bandung. The results of this study showed that both groups of students improved their open words vocabulary, and students who are taught through animation and video with learning in groups performed better than the students who learn individually, with pre-test scores of 59.59 and 59.00, and post-test scores of 83.47 and 73.63.